2004
DOI: 10.1021/ie030716d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ettringite in the Reuse of Hydrated Fly Ash from Fluidized-Bed Combustion as a Sulfur Sorbent:  A Hydration Study

Abstract: Waste from fluidized-bed combustion (FBC) has a low potential for reuse. One possibility for its recycling lies in a hydration process aimed at reactivating the SO 2 sorption ability of the unconverted lime. The formation of ettringite, as well as calcium hydroxide, in the hydrated FBC fly ash to be reinjected into the reactor could be of importance because ettringite is able to play a chemical and physical role in SO 2 capture. The aim of this paper is to investigate the conditions under which ettringite is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…They found that hydration at 70 • C for 48 h of the raw fly ash yields an ettringite-rich material, and ettringite represents the main source of free lime available for sulfur uptake as the reactivated ash is calcined. Bernardo et al [172] studied ettringite in more detail because it can play a chemical and physical role in capturing SO 2 . They investigated the conditions under which ettringite is formed by the liquid-phase hydration of FBC waste.…”
Section: So 2 Capturementioning
confidence: 99%
“…They found that hydration at 70 • C for 48 h of the raw fly ash yields an ettringite-rich material, and ettringite represents the main source of free lime available for sulfur uptake as the reactivated ash is calcined. Bernardo et al [172] studied ettringite in more detail because it can play a chemical and physical role in capturing SO 2 . They investigated the conditions under which ettringite is formed by the liquid-phase hydration of FBC waste.…”
Section: So 2 Capturementioning
confidence: 99%
“…Bernardo et al [ 50 ] have suggested that ettringite formation starts immediately during the first hours of hydration, and that the rate of its precipitation is limited only by the availability of the reactants. Ettringite forms at the expense of the dissolved Ca, sulphate and aluminium [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…The availability of Ca-sulfate is typically considered as the limiting reactant for ettringite formation in hydrated CFBC ashes [55]. However, the Ca-rich CFBC ash is low in reactive silica and aluminum, but rich in Ca-sulfate, and it can precipitate with ettringite concurrent gypsum [27,56].…”
Section: Discussionmentioning
confidence: 99%